2013
DOI: 10.1002/app.39747
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of chitosan‐g‐poly(acrylamide)/montmorillonite superabsorbent polymer composites: Studies on swelling, thermal, and antibacterial properties

Abstract: Superabsorbent composites based on chitosan-g-poly(acrylamide) and montorillonite (CTS-g-PAAm/MMT) were synthesized through in situ radical polymerization by grafting of crosslinked acrylamide onto chitosan backbone in presence of MMT at different contents. The formation of the grafted network was confirmed by attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR), thermogravimetric analysis (TGA), and differential scanning calorimetery (DSC). The obtained porous structure was observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 57 publications
2
40
0
1
Order By: Relevance
“…The degradation of the chitosan powder occurred at 329.5 °C (Table ), a temperature related to the depolymerization and pyrolitic decomposition of the polysaccharide. Similar data were observed by Ferfera‐Harrar et al . (298 °C) and by Neto et al .…”
Section: Resultssupporting
confidence: 59%
“…The degradation of the chitosan powder occurred at 329.5 °C (Table ), a temperature related to the depolymerization and pyrolitic decomposition of the polysaccharide. Similar data were observed by Ferfera‐Harrar et al . (298 °C) and by Neto et al .…”
Section: Resultssupporting
confidence: 59%
“…By comparing the relative intensity of C-O-C to N-H, it was observed that the value for PM5CHI was larger than those of PM5 and PM5cata, indicating the chemical grafting of PAM onto the chitosan backbone through etherification depicted in Scheme 3 (b). 19,50 (a) The presence of branched PAM, PAM-grafted-chitosan and the interfacial interactions within the nanocomposite hydrogels was confirmed by DSC results (Figure 4 (b)). The glass transition temperature (T g ) of the branched PAM synthesized at 60 o C was 198.2 o C, which was higher than the T g of the single-chain polyacrylamide nanoglobules (~191 o C) and the bulk polyacrylamide (188 o C), scanned at a rate of 20 o C. 51 These different T g values were attributable to the difference in chemical structure, chain entanglement degree 51 and experimental conditions.…”
Section: (A) (B)mentioning
confidence: 71%
“…Furthermore, the antimicrobial activity of PCL/OMMTs composite films could be explained due to migration of free ammonium surfactant from PCL nanocomposite films to culture medium because intercalation of PCL inside the organoclay structure could cause the release of part of the ammonium surfactant associated to the negatively charged part of the clay [53].…”
Section: Tga Analysismentioning
confidence: 98%